MOTIVATION IN LEARNING ENGLISH OF FIRST YEAR STUDENTS AT STUDY PROGRAM OF ENGLISH FACULTY OF CULTURAL STUDIES UNIVERSITAS BRAWIJAYA - ALFIANA, FAUZIAH (Fakultas Ilmu Budaya Universitas Brawijaya, 2013)
There are many factors that affect students’ succes in learning English, one of them is motivation. Motivation is one of important aspects needed by the students to achieve their learning objectives. This study is aimed at investigating the types of motivation in learning English, and the degree of motivation in learning English, and finding out the correlation between motivation of the first year students at Study Program of English Faculty of Cultural Studies Universitas Brawijaya and their achievement. This study used descriptive quantitative approach. The participants of this study were 70 students of the first year students at Study Program of English, Faculty of Cultural Studies, Universitas Brawijaya. The data were collected using Language Learning Orientations Scale– Intrinsic motivation, Extrinsic motivation, Amotivation Subscales (LLOS-IEA) questionnaire by Noels, Pelletier, Clement and Vallerand (2000) completed by the students and their grade point average of the first year. The result shows that extrinsic motivation and intrinsic motivation are preferred by the first year students at Study Program of English, Faculty of Cultural Studies, Universitas Brawijaya in which extrinsic motivation is more preferred motivation by the first year students (53%) than the intrinsic one (47%). It means that most of the first year students are extrinsically motivated to learn English since they are supported by their family, a peer group, or a society. In addition, there is a significant correlation between intrinsic motivation and students’ achievement (p: .001/r: .113). In conclusion, the first year students at Study Program of English, Faculty of Cultural Studies, Universitas Brawijaya are more extrinsically motivated in learning English although intrinsic motivation is correlated to the students’ achievement in their study. Therefore, it is suggested that the students’ motivation, especially intrinsic motivation in learning English be increased in order to achieve better result in their study. Keywords: motivation, achievement, extrinsic motivation, intrinsic motivation.